2011
DOI: 10.1007/s00436-011-2386-4
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy of the human low-density lipoprotein interaction with the tegument of Schistosoma mansoni

Abstract: The interaction between host molecules and Schistosoma mansoni has been regarded as a key feature for parasite survival. In this work, scanning electron microscopy was used to study the interaction of human low-density lipoprotein (LDL) with the tegument of the adult worm of S. mansoni. Worms were incubated in RPMI 1640 containing 10% of LPDS and 40 μg LDL/mL during 30, 60, and 120 min. Control worms were processed in the same way, without LDL. After the incubations, the samples were fixed and processed to sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 44 publications
0
13
0
1
Order By: Relevance
“…The tegument, a syncytium covered by two lipid bilayers that is a unique structure to all trematodes [46] – [49] . In fact the two lipid bilayer structure pertains only to trematodes that live within blood vessels [50] , plays vital roles like evasion of the immune system, acquisition of nutrients, excretion of catabolic products, targeted drug absorption and other physiological processes [47] , [49] , [51] [54] . Most of the drugs active against schistosomiasis damage the worm tegument, including praziquantel [55] , oxamniquine [56] , artemether [57] , mefloquine [34] , [58] , atorvastatin alone or in combination with medroxyprogesterone acetate [59] , and thioxo-imidazoline compounds [60] .…”
Section: Discussionmentioning
confidence: 99%
“…The tegument, a syncytium covered by two lipid bilayers that is a unique structure to all trematodes [46] – [49] . In fact the two lipid bilayer structure pertains only to trematodes that live within blood vessels [50] , plays vital roles like evasion of the immune system, acquisition of nutrients, excretion of catabolic products, targeted drug absorption and other physiological processes [47] , [49] , [51] [54] . Most of the drugs active against schistosomiasis damage the worm tegument, including praziquantel [55] , oxamniquine [56] , artemether [57] , mefloquine [34] , [58] , atorvastatin alone or in combination with medroxyprogesterone acetate [59] , and thioxo-imidazoline compounds [60] .…”
Section: Discussionmentioning
confidence: 99%
“…The entire worm is surrounded by a continuous cytoplasmic membrane, or syncytium, known as the tegument, composed of surface membrane, matrix and basal membrane, which is a unique structure of all trematodes. This structure is closely related to immune escape, nutrient uptake, excretion of catabolites, targeted drug absorption and other physiological processes (30)(31)(32), and most effective drugs against schistosomes would damage the tegument, including praziquantel (33), oxamycin (34) and artemisinin (35). After treatment with myricetin, S. japonicum's oral and abdominal suckers, sensory sensory papillae and on the surface, tegument and the reproductive organs were damaged to some extent, which may be due to the disruption of the osmotic pressure balance of the worm body, leading to changes in the body structure of the worm and eventually death.…”
Section: Discussionmentioning
confidence: 99%
“…The huge differences in development of S. japonicum between the WT and iNOS −/− rats clearly showed that NO could significantly influence the tegument structures, body size, and development of the reproductive organs in S. japonicum. The tegument is known to be required as essential protection for parasite survival during host immune attacks (23) and as a key structure for driving nutrient absorption and cholesterol metabolism (24,25). The modified structure of the tegument of S. japonicum in WT rats causes significant problems for the absorption of nutrients and the development of the parasite.…”
Section: Discussionmentioning
confidence: 99%